Systematic Review of Smartphone Apps as a mHealth Intervention to Address Substance Abuse in Adolescents and Adults. Issue 3 (July 2021) - Kazemi, Donna M.; Li, Shaoyu; Levine, Maureen J.; Auten, Beth; Granson, Matthew
Abstract : Supplemental digital content is available in the text. Abstract: Background: Substance abuse represents a foremost national concern for adolescents and adults; investigators have implemented a variety of interventions, delivered with both in-person and mobile-based apps' modalities. The electronic techniques could be more effective because they avoid the cost, privacy, and accessibility issues associated with in-person intervention. To address this issue, a systematic review of the scientific evidence relative to the efficacy of app-based interventions delivered by mobile devices (smartphones) to reduce substance abuse in adolescents and adults was carried out. Methods: To identify relevant studies published from 2005 to 2019, a comprehensive search was conducted. Databases that were searched include CINAHL, Cochrane CENTRAL, Embase, PsycINFO, PubMed, and Web of Science. Keywords and relevant controlled vocabulary terms related to substance abuse and technology were included. Studies were included if they had examined reductions in substance abuse and problem behaviors as a primary outcome with app-based interventions delivered to adolescents and adults. Results: The initial search yielded 21, 641 articles, duplicates were removed, and 14, 797 citations remained; title/abstract screening yielded 190 full-text articles. One hundred seventy-three were excluded because they did not meet the inclusion criteria, leaving 17 final articles to be analyzed in this review. Use of app-based interventions showed some evidence of effectiveness in reducing substance abuse in the adolescent adult population. Conclusion: Most intervention studies analyzed focused on alcohol reduction. Further research is needed on diverse substance abuse utilizing larger sample sizes, longitudinal studies, and theoretical foundations on the practice of delivering interventions using mobile-based apps.